Aspectos determinantes que interferem para a evasão de discentes: um estudo com ex-alunos do curso de Ciências Contábeis em uma Instituição de ensino superior confessional - Albanez, Rogério (2017)
The school evasion factor, historically, occurs at all levels and types of education, causing social, economic, political, academic and financial damages to all those committed to education. The evasion phenomenon in universities has caused great disquiet in general. Failure to complete an undergraduate degree is detrimental to the student, the university and the community. This study examined both the profiles of the students that chose to take the Accounting Science degree at the Adventist University Center of São Paulo-UNASP, Campus São Paulo, and the reasons that led them to give up finishing their degree. The aim of this study was to call the university’s attention to the need to detect adjustments or changes necessary to better identify the factors that contribute to students' dissatisfaction related to the Accounting Sciences degree, establishing the reasons that led them to give up, such as their disinterest in the degree itself, and to demonstrate what the university is doing or could do, for example, to assign more qualified professors to teach the degree’s core courses, in order to avoid or reduce the occurrence of evasion. The research method used to obtain the necessary data was qualitative analysis, presenting references of other researches on the evasion factor in two perspectives: first, looking at the evasion phenomenon in several undergraduate courses at different universities in Brazil and second, looking at the event focusing exclusively on the Accounting Sciences degree at several universities scattered throughout the country. To complete the analysis, questionnaires were applied to the evaded students and to UNASP’s Accounting Sciences’ degree coordinator. The research showed that the major cause of evasion is the economic-financial factor. The lack of motivation and disillusionment with the degree was another very important factor, followed by other personal, institutional reasons and then others, such as health reasons